Effects of craniosacral therapy as adjunct to standard treatment for pelvic girdle pain in pregnant women: a multicenter, single blind, randomized controlled trial. (4th March 2013) - Elden, Helen; Östgaard, Hans‐Christian; Glantz, Anna; Marciniak, Pia; Linnér, Ann‐Charlotte; Olsén, Monika Fagevik
Abstract: Objective: Pelvic girdle pain (PGP) is a disabling condition affecting 30% of pregnant women. The aim of this study was to investigate the efficacy of craniosacral therapy as an adjunct to standard treatment compared with standard treatment alone for PGP during pregnancy. Design: Randomized, multicenter, single blind, controlled trial. Setting: University hospital, a private clinic and 26 maternity care centers in Gothenburg, Sweden. Population: A total of 123 pregnant women with PGP. Methods: Participants were randomly assigned to standard treatment (control group, n  = 60) or standard treatment plus craniosacral therapy (intervention group, n  = 63). Main outcome measures: Primary outcome measures: pain intensity (visual analog scale 0–100 mm) and sick leave. Secondary outcomes: function (Oswestry Disability Index), health‐related quality of life (European Quality of Life measure), unpleasantness of pain (visual analog scale), and assessment of the severity of PGP by an independent examiner. Results: Between‐group differences for morning pain, symptom‐free women and function in the last treatment week were in favor of the intervention group. Visual analog scale median was 27 mm (95% confidence interval 24.6–35.9) vs. 35 mm (95% confidence interval 33.5–45.7) ( p  = 0.017) and the function disability index was 40 (range 34–46) vs. 48 (range 40–56) ( p  = 0.016). Conclusions: Lower morning pain intensity and less deteriorated function was seen after craniosacral therapy in conjunction with standard treatment compared with standard treatment alone, but no effects regarding evening pain and sick‐leave. Treatment effects were small and clinically questionable and conclusions should be drawn carefully. Further studies are warranted before recommending craniosacral therapy for PGP.